Implications of travel behavior determinants on transportation planning in the COVID-19 pandemic - Lim, Ma. Bernadeth B.; Lim, Hector R., Jr.; Anabo, Joy Mae (2022)
Transportation planning is vital in the current scenario of rapidly growing populations, travel changes, and demand. With the emergence of the COVID-19 pandemic, socio-economic conditions in society are exerting significant strain on transportation infrastructure. These conditions might affect not only the transport demand and infrastructure but also the travel behavior of people. This paper aims to analyze their travel behavior and predict their response to changes in the travel environment, using recent literature on modeling travel patterns in a pandemic. It also analyzes the implications of significant factors to transport planning. Understanding and anticipating travel behavior and its impact on transportation planning in the pandemic condition is crucial in transportation modeling, making decisions, and formulating policies based on travel demands.
Keywords: Transport planning; COVID-19 pandemic